Reinstatement of Kalanchoe stearnii (Crassulaceae subfam. Kalanchooideae; K. subg. Kalanchoe), a small-growing, rotundifolioid species, likely from southern Africa - Smith, Gideon F. (Phytotaxa, 2023)
Following the recent refinement of the circumscription of Kalanchoe rotundifolia (Crassulaceae subfam. Kalanchooideae), K. stearnii is here reinstated as an accepted species. Kalanchoe stearnii is separated from K. rotundifolia, from which it differs by having shiny, light green, narrowly obovate leaves, and the adaxial corolla lobe surface that is yellow, while plants of K. rotundifolia are glaucous to dull light yellowish green, with the adaxial corolla lobe surface dull red to orange.